Analisis Kinerja Keuangan UMKM dengan Menggunakan Metode Fintech Aplikasi Keuangan : (Studi Kasus Desa Sambirejo Timur) - Fitria Sani; Eddi Suprayitno; Jurkarnain Jurkarnain (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to see how the Si Apik android-based application can be applied to MSMEs to meet the needs of the accounting system when they make financial statements. This study studies the Micro Enterprises of East Samirejo Village located in Ercut Sei Tuan District. This Micro Business has an Android smartphone with at least 3GB of RAM and has been operating for at least three years. Micro Enterprises may also not have financial records manually. Qualitative descriptive research is of its kind. Data and information collection techniques include observation, interviews, and documentation with data analysis. The results of the study show that Micro Business actors can use the Si Apik application to record transactions and report finances easily and simply. The app can also be used on a daily basis, and micro entrepreneurs can report their finances with standards, which makes it easier for them to apply for capital loans to financial institutions.